(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Bangladesh is one of the developing countries where the maternal mortality is extraordinarily high. Objectives: This study was conducted to find out the number and cause of obstetric haemorrhage related maternal death. Methodology: This retrospective study was conducted in the department of obstetrics & gynaecology at M.A.G Osmani Medical College Hospital, Sylhet, Bangladesh from January 2006 to December 2007. From all maternal deaths related to pregnancy occurred in that period, only death due to obstetric hemorrhage were enrolled. Thereafter, the records of hemorrhage related death patients were scrutinized and data were collected from death register. All necessary information was collected in a pre-designed clinical data sheet and analyzed. Results: Among all deaths in obstetric unit, maternal mortality due to obstetric haemorrhage was 32.09%. The deaths were common among multipara (3-4) in 26-30 years age group. Most of them were from lower socio-economic condition having no or irregular antenatal checkup. Among the causes of obstetric haemorrhage, PPH was the commonest. Atonic uterus was the main cause of PPH. Injudicious use of oxytocin and obstructed labour were the common cause of rupture of uterus. Although the causes of haemorrhage were different, most of the patients died due to haemorrhagic shock. Conclusion: This study helps to detect the magnitude of problem and major causes of maternal deaths specially haemorrhage related maternal deaths. Journal of Current and Advance Medical Research, July 2021;8(2):90-94